Optimized Sample Preparation for Tandem Capillary Electrophoresis Single-Stranded Conformational Polymorphism/Heteroduplex Analysis. (August 2002) - Kourkine, Igor V.; Hestekin, Christa N.; Magnusdottir, Soffia O.; Barron, Annelise E.
Here we describe DNA sample preparation methods that allow the rapid, simultaneous generation of both single-stranded conformational polymorphism (SSCP) and heteroduplex DNA elements from a single sample in a single tube, which are suitable for direct injection into a capillary electrophoresis (CE) instrument with excellent sensitivity of genetic mutation detection. The p53 gene was used as a model DNA region for this study, which was performed on a high-throughput MegaBACE™ 96-capillary array electrophoresis instrument. We found that, contrary to the practice common in slab-gel SSCP analysis, denaturants such as formamide are incompatible with this novel technique because they result in homo- and heteroduplex peak broadening in CE (possibly as a result of incomplete dsDNA re-hybridization) that reduces the peak resolution and hence the sensitivity of mutation detection. We also have found that PCR buffers, which are typically used to suspend samples for slab-gel heteroduplex analysis (HA), but which are less suitable for CE because of the presence of extra salt that reduces the efficiency of electrokinetic injection, may be substituted with a 10 mM Tris-HCl buffer (pH 8.5). The use of this Tris-HCl buffer for sample preparation provides both a high sensitivity of mutation detection by tandem SSCP/HA and high efficiency of electrokinetic injection by CE. In a related study (published elsewhere), we have applied this optimized protocol to the screening of a set of 32 mutant DNA samples from p53 exons 7 and 8 and recorded 100% sensitivity of mutation detection for tandem CE-SSCP/HA, whereas each individual method yielded lower sensitivity on its own (93% for SSCP and 75% for HA).